2018
DOI: 10.4309/jgi.2018.38.11
|View full text |Cite
|
Sign up to set email alerts
|

Sports Bettors: A Systematic Review

Abstract: Sports betting is associated with problematic gambling behaviours. However, little is known about the profile of sports bettors. Also, it is still unclear if there are useful abilities in sports betting. This systematic review aims to describe gambling habits and cognitions of sports bettors, and determine the roles of chance and skill in sports betting. Addressing the chance and skill distinction in sports betting would be helpful to identify which of sports bettors' cognitions are erroneous. Out of 991 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
1
7
0
7
Order By: Relevance
“…In a study of 258 individuals, Khazaal et al ( 2012 ) reported that experts (i.e., professional soccer players, coaches, or journalists) were no more successful at predicting soccer match outcomes than the non-professionals. In systematic review carried out on the role of chance and skill in sports bettors (and focusing on cognitions in the behaviour), Mercier et al ( 2018 ) reported that sports bettors overestimated the importance of skill on the overall match outcome. Ladouceur, Giroux and Jacques ( 1998 ) found that gamblers on horse races who were classed as ‘experts’ picked more winning selections but did not have better monetary outcomes than random selection.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 258 individuals, Khazaal et al ( 2012 ) reported that experts (i.e., professional soccer players, coaches, or journalists) were no more successful at predicting soccer match outcomes than the non-professionals. In systematic review carried out on the role of chance and skill in sports bettors (and focusing on cognitions in the behaviour), Mercier et al ( 2018 ) reported that sports bettors overestimated the importance of skill on the overall match outcome. Ladouceur, Giroux and Jacques ( 1998 ) found that gamblers on horse races who were classed as ‘experts’ picked more winning selections but did not have better monetary outcomes than random selection.…”
Section: Discussionmentioning
confidence: 99%
“…Grundsätzlich ist festzuhalten, dass sich weitaus mehr Männer als Frauen für Sportwetten begeistern [2,18]. Wird der Fokus auf ein problematisches Sportwettverhalten gelegt, kristallisieren sich international studienübergreifend folgende personenbezogene Merkmale als Risikofaktoren heraus: männliches Geschlecht, eher jüngeres Lebensalter, Single-Dasein, Überschätzung der Einflussnahme auf das Wettergebnis im Sinne kognitiver Verzerrungen sowie ein erhöhtes Konsumausmaß im Hinblick auf legale und illegale Drogen [2].…”
Section: Individuum: Zentrale Risikofaktorenunclassified
“…Demgemäß kommt auch ein systematischer Review zu der Schlussfolgerung, dass Sportwettende den Einfluss des Zufalls auf ihren Wetterfolg minimieren bzw. ihre persönliche Einflussnahme aufgrund bestimmter vermeintlicher Fähigkeiten und Fertigkeiten überschätzen [18]. Vor allem Prozesse der aktiven Einbindung, angefangen mit der Suche nach sportrelevanten Informationen und der Analyse von Statistiken bis hin zur Auswahl der Wettereignisse, implizieren ein hohes Ausmaß an Freiheitsgraden und suggerieren wohlbegründete Entscheidungsprozesse auf einer scheinbar faktischen Basis.…”
Section: Individuum: Zentrale Risikofaktorenunclassified
“…Sports wagering consists of betting on individual sporting events or contests, through fantasy sports (seasonal or daily), or on individual players or events through prop bets or inplay sports betting 3 4. It may occur among peers, through a bookmaker (individuals accepting illegal wagers or gaming operators where legal) or through online sites.…”
Section: Introductionmentioning
confidence: 99%
“…It may occur among peers, through a bookmaker (individuals accepting illegal wagers or gaming operators where legal) or through online sites. Sports wagering has grown in popularity, with the total amount of money wagered yearly increasing 3 5–9. A US consumer survey revealed that 42% of adults report having placed a sports wager during their lifetime,10 with 4% doing so regularly 10…”
Section: Introductionmentioning
confidence: 99%